Doppler backscattering for spherical tokamaks and measurement of high-k density fluctuation wavenumber spectrum in MAST. (23rd June 2015) - Hillesheim, J.C.; Crocker, N.A.; Peebles, W.A.; Meyer, H.; Meakins, A.; Field, A.R.; Dunai, D.; Carr, M.; Hawkes, N.
Abstract: The high- k ( ) wavenumber spectrum of density fluctuations has been measured for the first time in MAST (Lloyd et al 2003 Nucl. Fusion 43 1665). This was accomplished with the first implementation of Doppler backscattering (DBS) for core measurements in a spherical tokamak. DBS has become a well-established and versatile diagnostic technique for the measurement of intermediate- k (, and higher) density fluctuations and flows in magnetically confined fusion experiments. Previous implementations of DBS for core measurements have been in standard, large aspect ratio tokamaks. A novel implementation with two-dimensional (2D) steering was necessary to enable DBS measurements in MAST, where the large variation of the magnetic field pitch angle presents a challenge. We report on the scattering considerations and ray tracing calculations used to optimize the design and present data demonstrating measurement capabilities. Initial results confirm the applicability of the design and implementation approaches, showing the strong dependence of scattering alignment on the toroidal launch angle and demonstrating that DBS is sensitive to the local magnetic field pitch angle. We also present comparisons of DBS plasma velocity measurements with charge exchange recombination and beam emission spectroscopy measurements, which show reasonable agreement over most of the minor radius, but imply large poloidal flows approaching the magnetic axis in a discharge with an internal transport barrier. The 2D steering is shown to enable high- k measurements with DBS, at cm ( ) for launch frequencies less than 75 GHz; this capability is used to measure the wavenumber spectrum of turbulence and we find for –11, which is similar to the expectation for the turbulent kinetic cascade of .